find the value


This topic contains 1 reply, has 2 voices, and was last updated by  Subrata Ghosh 1 month ago.

Viewing 2 posts - 1 through 2 (of 2 total)
  • Author
  • #21316

    swastik pramanik

    What is the value of \(\frac{b}{(a-c)(a-b)} + \frac{c}{(b-c)(b-a)} + \frac{a}{(c-a)(c-b)}\) ?


    Subrata Ghosh

    There seems to be nothing special about the given expression since the cyclic symmetry is not present. So it is not an identity with constant value for all a,b,c.

    So, we can have variable value of the expression depending on the values of a,b and c. For example, for a=0,b=1 and c=2 the sum is -1.5 and that for a=1, b=4 and c=2 is 1.167.

    Restoring cyclic symmetry in the above expression will give us the following identity :
    a/(a−c)(a−b)+b/(b−c)(b−a)+c/(c−a)(c−b) = 0

    This can be proved by simple addition of the LHS.

Viewing 2 posts - 1 through 2 (of 2 total)

You must be logged in to reply to this topic.